2012
DOI: 10.1016/j.intimp.2012.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Ocimum gratissimum Linn. and rosmarinic acid, attenuate eosinophilic airway inflammation in an experimental model of respiratory allergy to Blomia tropicalis

Abstract: Allergic asthma has emerged as an important public health problem of urban populations in developed countries. Very often herbal medicine is used to treat this widespread disease, due to the lack of efficacy and the important side effects related to the classical drugs in use. Along this line, Ocimum gratissimum (Og) is a plant widely used in Brazilian folk medicine to treat inflammatory disorders, such as asthma. In the present study we evaluated the immunomodulatory effects of Og and rosmarinic acid (RA, a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 39 publications
2
33
0
3
Order By: Relevance
“…This seems to be approximately to RA founded value. This result is comparable to that found by Costa et al [37] in methanolic extract of O. gratissimum from Brazil.…”
Section: High Performance Liquid Chromatography (Hplc) Analysissupporting
confidence: 90%
“…This seems to be approximately to RA founded value. This result is comparable to that found by Costa et al [37] in methanolic extract of O. gratissimum from Brazil.…”
Section: High Performance Liquid Chromatography (Hplc) Analysissupporting
confidence: 90%
“…1) Its dried inflorescence and roots have a long history of use in traditional Chinese and European medicine. 2) P. vulgaris has been reported to exhibit numerous pharmacological and biological properties, including antibacterial, 3) anticancer, 4) antihemorrhagic, 5) anti-human immunodeficiency virus (HIV), 6) anti-inflammatory, 7) antioxidant, 8) antiproliferative, 9) antidiabetic, 10) antiviral, 11) hepatoprotective, 12) immunomodulatory, 13) and neuroreparative 3) activities. Chemical investigations have revealed that P. vulgaris contains a variety of bioactive constituents, primarily rosmarinic acid (RA), ursolic acid, and oleanolic acid.…”
mentioning
confidence: 99%
“…A recent study has revealed that rosmarinic acid, a polyphenolic compound, showed anti-inflammatory activity in the treatment of allergic asthma [23]. The furanocoumarins also exert anti-inflammatory activities by inhibiting NO and PGE 2 production, and among these compounds, imperatorin showed the most potent inhibitory activity [24-27].…”
Section: Discussionmentioning
confidence: 99%